Inter-relationship between sphingosine kinase and phospholipase D in signaling Arabidopsis response to abscisic acid - Guo, Liang; Mishra, Girish; Markham, Jonathan E.; Li, Maoyin; Tawfall, Amanda; Welti, Ruth; Wang, Xuemin (My University, 2012)
Phosphatidic acid (PA) and phytosphingosine-1-phosphate (phyto-S1P) both are lipid messengers involved in plant response to abscisic acid (ABA). Our previous data indicate that PA binds to sphingosine kinase (SPHK) and increases its phyto-S1P-producing activity. To understand the cellular and physiological functions of the PA-SPHK interaction, we isolated Arabidopsis thaliana SPHK mutants sphk1-1 and sphk2-1 and characterized them, along with phospholipase Dα1 knockout, pldα1, in plant response to ABA. Compared to wild-type (WT) plants, the SPHK mutants and pldα1 all displayed decreased sensitivity to ABA-promoted stomatal closure. Phyto-S1P promoted stomatal closure in sphk1-1 and sphk2-1, but not in pldα1, whereas PA promoted stomatal closure in sphk1-1, sphk2-1, and pldα1. The ABA activation of PLDα1 in leaves and protoplasts was attenuated in the SPHK mutants, and the ABA activation of SPHK was reduced in pldα1. In response to ABA, the accumulation of long-chain base phosphate (LCBP) was decreased in pldα1 whereas PA production was decreased in SPHK mutants, compared WT. Collectively, these results indicate that SPHK and PLDα1 act together in ABA response and that SPHK and phyto-S1P act upstream of PLDα1 and PA in mediating the ABA response. Whereas SPHKs are involved in the activation of PLDα1, the activity of PLDα1 further enhances SPHK activation via PA binding SPHKs. The data suggest that SPHK/phyto-S1P and PLDa1/PA are co-dependent in amplification of response to ABA, mediating stomatal closure in Arabidopsis.
Keywords: Abscisic acid; Phosphatidic acid; Signal transduction; Sphingosine 1-phosphate; Stress response; PA-protein interaction; Lipid signaling; Sphingosine kinase